Pengaruh Pelatihan Crossover Medicine Ball Terhadap Pukulan Long Stroke pada Atlet Woodball - I Kadek Nuprianta Putra; I Ketut Semarayasa; Kadek Yogi Parta Lesmana (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This study aimed to analyze the effect of medicine ball crossover training on improving long stroke hitting performance in Pekan Olahraga Pelajar Buleleng woodball athletes. The study design used a pretest-posttest control group design with 30 athletes as samples, consisting of an experimental group and a control group of 15 people each. The medicine ball crossover training program was carried out for eight weeks with a frequency of three times per week. The results showed that the experimental group experienced an increase in the average hitting distance from 73.40 meters (SD = 7.39) in the pretest to 81.80 meters (SD = 2.51) in the posttest. The average accuracy score also increased from 72 to 84. The paired samples t-test proved a significant difference in the experimental group between the pretest and posttest (p <0.001), both in terms of distance and hitting accuracy. These results support that medicine ball crossover training is effective in increasing rotational strength and core muscle coordination, thus supporting the long stroke hitting performance of woodball athletes optimally. This method is recommended to be integrated into the woodball athlete development program as an alternative to scientific training-based training.